Increasing The Students’ Ability In Speaking English By Using Work In Pair Strategy - Riswan Zega; Destina Adventri Hulu (Educativo: Jurnal Pendidikan, 2022)
This research aimed to increase the students’ ability in speaking by using Work in Pair strategy at the grade VII class B of SMP Swasta St. Theresia Lahewa. In this research the researcher applied the Classroom Action Research with some stages namely planning, observation, action and reflection. It has been conducted in SMP Swasta St. Theresia Lahewa at the grade VII, class B, consisted 30 students. This research has been applied in two cycles because in the first cycle the students still did not pass Minimum Competence Criteria (MCC), 75. The instrument of data colection were observation sheets, fieldnote, and test by video recording. After analyzing the data, the result showed in Cycle I there were 6 students (20%) who got mark in renge 40-59. They were classified in low level. Then 21 students (70%) got mark in range 60-74. They were classified in adequate level. And then 3 (10%) students who got mark in range 75-84 classified in good level. The average of students’ mark was 55 while the highest mark was 76 and the lowest mark was 41. Then in Cycle II there were 21 students (80%)  who got the mark in range 75-84, were classified as good level and 6 (20%) got mark in range 85-100, were classified in high level. The average of students’ mark was 80. Then, the highest mark was 90 and the lowest was 76. It can be concluded that Work in Pair strategy increased the students’ ability in speaking English.